Leverage constraints and real interest rates - Jukka Isohätälä; Feo Kusmartsev; Alistair Milne; Donald Robertson (Bank of Finland, 2014)
This paper investigates the macroconomics of real interest rates when there are constraints on debt finance, used both for insurance against income shocks and transferability of resources over time. We amend a standard continuous-time deterministic model of international exchange, with patient and impatient countries, introducing country level shocks fully diversifiable at the global level. A series of shocks that push one country towards its leverage limit induces substantial pre-cautionary saving and a collapse of real interest rate relative to the deterministic benchmark. We discuss the resulting dynamics of interest rates and the broader implications for macroeconomic modelling.
URN:NBN:fi:bof-201411193264
Keywords: E44; 330; borrowing constraints; debt management; incomplete financial markets; international macroeconomics; finance and macroeconomics; macroeconomic propagation; precautionary saving; systemic risk